Citrobacter koseri Septicaemia in a Holstein Calf - Komine, M.; Massa, A.; Moon, L.; Mullaney, T. (Journal of comparative pathology, 2014)
A 4-day-old male Holstein calf with dull mentation, nystagmus and blindness was humanely destroyed and subject to necropsy examination. Gross lesions included severe suppurative meningitis characterized by diffuse cloudy thickening of the meninges, bilateral hypopyon and fibrinosuppurative polyarthritis affecting the hocks. Citrobacter koseri was isolated from the meninges, ocular fluid, synovial fluid, spleen and small intestine. Microscopically, there was neutrophilic and histiocytic meningitis with intralesional bacilli, endophthalmitis, neutrophilic splenitis and multiple renal microabscesses. Failure of passive transfer of colostrum was confirmed. This appears to be the first characterization of septicaemia in a calf caused by C. koseri, with lesions comparable with those described in human neonates.